Differences in the Distribution of Species, Carbapenemases, Sequence Types, Antimicrobial Heteroresistance and Mortality Rates Between Pediatric and Adult Carbapenemase-Producing Enterobacterales in Bloodstream Infections - Yu, Hanbing; Ma, Deyu; Liu, Bo; Yang, Suqing; Lin, Qiuxia; Yu, Renlin; Jia, Xiaojiong; Niu, Siqiang; Zhang, Qun; Huang, Shifeng (Frontiers in Medicine, 2022)
The dissemination of carbapenemase-producing Enterobacterales (CPE) is worrisome given their scarce treatment options. CPE bloodstream infections (BSIs) had a high mortality rate in adults, and there was little data on paediatric CPE-BSIs around the world. We comprehensively explored the differences in the clinical and microbiological characteristics between pediatric and adult CPE-BSIs. 48 pediatric and 78 adult CPE-BSIs cases were collected. All-cause 30 day-mortality in children with CPE-BSIs (14.6%, 7/48) was significantly lower than that in adult patients (42.3%, 33/78, p=0.001). The subgroup in adults empirically treated with tigecycline as an active drug displayed a significantly higher 30-days crude mortality (63.3%, 19/30) than the subgroup treated without tigecycline (29.2%, 14/48, p=0.003). K. pneumoniae was the most prevalent species in both the pediatric (45.8%, 22/48) and adult populations (64.1%, 50/78), with discrepant carbapenemase genes in each population: 95.4% (21/22) of the pediatric K. pneumoniae isolates carried blaNDM, while 82.0% (41/50) of the adult strains harbored blaKPC. The ratio of E. coli in children (37.5%) was significantly higher than that in adults (12.8%, p=0.002). In both populations, the majority of E. coli expressed blaNDM, particularly blaNDM-5. With statistical significance, blaNDM was much more common in children (95.8%, 46/48) than in adults (34.6%, 27/78). The rate of multiple-heteroresistance phenotypes in children was as high as 87.5%, which was much lower in adults (57.1%). Agar dilution checkboard experiment against one pediatric carbapenemase-producing E. coli isolates showed that the combination of amikacin and fosfomycin yielded an additive effect. Overall, K. pneumoniae was the most common CPE-BSIs pathogen in both populations, with NDM-producing K. pneumoniae and KPC-producing ST11 K. pneumoniae being the most prevalent species in children and adults, respectively. E. coli was more prevalent in children than in adults, yet blaNDM-5 was the most common carbapenem-resistant mechanism in E. coli in both populations. The wide range of multiple-heteroresistance combination traits found in different pathogen species from different host populations should provide a good foundation for future combination therapy design. Further investigations from more CPE isolates of various species are needed to evaluate the possible in vitro partial synergy of the amikacin and fosfomycin combination.